HISTORY AND RESULTS OF BREEDING OF BEAN VEGETABLE ON THE VEGETABLE VORONEZH EXPERIMENTAL STATION - S. N. Derevschyukov (Овощи России, 2015)
The main results  of breeding  of vegetable  bean in the Voronezh Vegetable Research  Station are shown. Several varieties of vegetable bean are described.